Development and Implementation of U.S. Army Guidelines for Managing Soldiers at Risk of Suicide. (21st March 2019) - Hoyt, Tim; Repke, Diana M
Abstract: Objectives: Despite significant efforts in suicide prevention over the past several years, suicide rates in the U.S. Army remain largely unchanged. This paper describes a collaborative effort between line-unit leaders, medical personnel, and installation services to synchronize suicide risk identification and communication between these disparate entities. Methods: Under the direction of the Installation Director of Psychological Health at Joint Base Lewis-McChord, a Behavioral Health Process Action Team was chartered to identify best practice and formulate policy for identifying and managing service members at risk for suicide. Results: Compliance with the new policy reached 100% within 6 months of implementation, as measured by peer review of records. This installation policy was subsequently identified as a best practice and adopted Army-wide as the standard of practice. Discussion: Knowledge transfer of research findings into policy and practice is crucial for suicide prevention. The current policy shows good integration of current research with practice in military settings. Conclusions: Combined efforts in crafting policy for risk identification and communication resulted in a policy that was acceptable and feasible from the perspective of commanders and clinicians. Synchronization efforts between commanders, clinicians, and support services are crucial to ensure effective intervention to prevent suicide behavior.